2008
DOI: 10.1177/1076029607308390
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine Activates Platelets In Vitro

Abstract: is very common, and these has been reported to be a risk factor for arterial and venous thromboses. The study of Leiden thrombophilia established hyperhomocysteinemia (above the 90th percentile) as a risk factor for deep-vein thrombosis. 4 A further metaanalysis showed that a 5 μmol/L elevation in HCY was associated with a 27% higher risk of venous thrombosis in prospective studies and 60% higher risk of venous thrombosis in retrospective studies. Genotype studies of the methylenetetrahydrofolate reductase enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 44 publications
(60 reference statements)
1
19
0
Order By: Relevance
“…Hyperhomocysteinemia has been associated with decreased platelet counts in individuals with the MTHFR 677TT genotype (Rongioletti et al 2005). Also, in a study of the activation of platelets by homocysteine in vitro, platelet counts and homocysteine concentration were inversely proportional, an observation attributed to the clumping of activated platelets, rendering them unavailable for counting (Mohan et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperhomocysteinemia has been associated with decreased platelet counts in individuals with the MTHFR 677TT genotype (Rongioletti et al 2005). Also, in a study of the activation of platelets by homocysteine in vitro, platelet counts and homocysteine concentration were inversely proportional, an observation attributed to the clumping of activated platelets, rendering them unavailable for counting (Mohan et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we may propose that homocysteine; RPR and MPV are involved in the course of the inflammation. Similarly, it was indicated that the homocysteine promoted platelet activation [17,18] division of hematopoietic cells consist seen in vitamin B12 deficiency leads to defects in DNA synthesis. RDW indicates heterogeneity and equivalent of anisocytosis of red blood cell.…”
Section: Discussionmentioning
confidence: 97%
“…It is well known that the level of homocysteine in serum increased in patients with vitamin B12 deficiency. The increasing homocysteine pathway leads to inflammation in patients with vitamin B12 deficiency [17].…”
Section: Discussionmentioning
confidence: 99%
“…An inverse relationship has been demonstrated between IMT and mean cerebral blood flow velocity (mCBFV), with decreased CBFV corresponding to elevated IMT [21]. In addition, Mohan et al [22] suggested that exposure to Hcy could induce platelet activation and hypercoagulability. Since platelet activating factor can reduce reducing coronary blood flow [23], these results indicate that Hcy may affect hemodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained in this study showed that at Hcy levels below 15 μmol/L, increased Hcy was related to decreased hemodynamics, while Hcy levels higher than 15 μmol/L were positively correlated with hemodynamics. This is due to the fact that Hcy is responsible for the hypercoagulability status of blood [22], and so it can reduce blood flow velocity. Hemodynamics is positively associated with carotid stenosis and carotid stenosis could result from HHcy [25].…”
Section: Discussionmentioning
confidence: 99%